Dynamic Simulation of a 1MWe CSP Tower Plant with Two-level Thermal Storage Implemented with Control System. (May 2015) - Liu, S.J.; Faille, D.; Fouquet, M.; El-Hefni, B.; Wang, Y.; Zhang, J.B.; Wang, Z.F.; Chen, G.F.; Soler, R.
Abstract: The study is carried out in the framework of cooperation between IEE-CAS and EDF R&D since 2012 on the Badaling 1MWe concentrated solar tower power plant located in the suburb of Beijing. The paper first presents a dynamic model of the power plant, in which Modelica library 'ThermoSysPro' was applied under the simulation environment Dymola ® . The model comprises sun to power generation loop and thermal storage system including two tanks oil and a steam accumulator. A detailed shell and tube steam-oil sectional heat exchanger has been modeled and implemented to simulate the heat transfer performance. By doing this, storage charging and releasing procedure could be predicted delivering transient behaviors of the upstream and downstream steam quality. A two-level control design on the Matlab/Simulink ® was developed and tested on the detailed Dymola ® model. For realizing the coupling of two simulation tools, different approaches, were attempted, among which OPC server structure is suggested and presented in detail in this paper.